A STUDY ON THE ABILITY OF THE SECOND GRADE STUDENTS OF SMA PGRI PEKANBARU IN WRITING DESCRIPTIVE TEXTS - Dina Sulastry Br Lubis Sulastry Br Lubis; Hadriana '; Atni Prawati Prawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This descriptive research were intended to find out the ability of the second grade students of SMA PGRI PEKANBARU in writing descriptive texts. The sample of this research were 30 students that was taken by using cluster sampling. And, the data was collected by giving written test. The test was scored based on Hughes’s assessment for all writing aspects including grammar, vocabulary, mechanics, organization, and fluency. Based on the students’ score, the level ability of the second grade students of SMA PGRI PEKANBARU in writing descriptive texts is good by getting 64 at the average score. In description, there is one student (3%) who got excellent level by getting 85 score. Then, 18 students (60%) reached good level and 11 students (37%) reached mediocre level. None of students are in poor and very poor level. Moreover, the students are still lack of practiced in writing descriptive text for each writing aspects. Most of them lacked of vocabularies and fluency aspects, but they are good at organization and mechanic aspects. Therefore, the researcher concluded that the ability of the second grade students of SMA PGRI PEKANARU in writing descriptive texts is good and they need to be more practiced in writing.Keywords: Hughes’ Assessments, Descriptive Text, Students’ Writing Ability